On Large Volume Moduli Stabilization in IIB Orientifolds - Walliser, N.-O. (Український фізичний журнал, 2010)
I present a brief introduction to the construction of explicit type IIB orientifold compactifications and summarize the ‘Large Volume Scenario’ on compact four-modulus Calabi–Yau manifolds. I discuss the relevance of this kind of setups for the physical MSSMlike model building and gravitational cosmology. These notes are based on my talk at the ‘Bogolyubov Kyiv Conference 2009’ on ‘Modern Problems of Theoretical and Mathematical Physics’. Подано короткий вступ до побудови явних компактифiкацiй IIБ орiєнтованих множин та розглянуто “сценарiй великих об’ємiв” для компактних чотиримодульних Калабi–Яу многовидiв. Обговорено доречнiсть таких схем для побудови фiзичної моделi МССМ-типу та для гравiтацiйної космологiї. Основою роботи є доповiдь на “Боголюбовськiй київськiй конференцiї 2009” з “Сучасних проблем теоретичної та математичної фiзики”.